GM-CSF production by glioblastoma cells has a functional role in eosinophil survival, activation and growth factor production for enhanced tumor cell proliferation - Curran, Colleen S. (2011)
Medicinal interventions of limited efficacy are currently available for the treatment of glioblastoma multiforme (GBM), the most common and lethal primary brain tumor in adults. The eosinophil is a pivotal immune cell in the pathobiology of atopic disease that is also found to accumulate in certain tumor tissues. Inverse associations between atopy and GBM risk suggest that the eosinophil may play a functional role in certain tumor immune responses. To assess the potential interactions between eosinophils and GBM, human primary blood eosinophils were cultured with two separate human GBM-derived cell lines (A172, U87-MG) or conditioned media generated in the presence or absence of TNF-α. Results revealed differential eosinophil adhesion and increased survival in response to co-culture with GBM cell lines. Eosinophil responses to GBM cell line-conditioned media included increased survival, activation, CD11b expression and S100A9 release. Addition of GM-CSF neutralizing antibodies to GBM cell cultures or conditioned media reduced eosinophil adhesion, survival and activation, linking tumor cell-derived GM-CSF to the functions of eosinophils in the tumor microenvironment. Dexamethasone, which has been reported to inhibit eosinophil recruitment and shrink GBM lesions on contrast enhanced scans, reduced the production of tumor cell-derived GM-CSF. Furthermore, culture of GBM cells in eosinophil-conditioned media increased tumor cell viability, and generation of eosinophil-conditioned media in the presence of GM-CSF enhanced the effect. These data support the idea of a paracrine loop between GM-CSF producing tumors and eosinophil-derived growth factors in tumor promotion/progression.